Metabolomic markers and physiological adaptations for high phosphate utilization efficiency in rice. (7th July 2020) - Watanabe, Mutsumi; Walther, Dirk; Ueda, Yoshiaki; Kondo, Katsuhiko; Ishikawa, Satoru; Tohge, Takayuki; Burgos, Asdrubal; Brotman, Yariv; Fernie, Alisdair R; Hoefgen, Rainer; Wissuwa, Matthias
Abstract: Utilizing phosphate more efficiently is crucial for sustainable crop production. Highly efficient rice ( Oryza sativa ) cultivars have been identified and this study aims to identify metabolic markers associated with P utilization efficiency (PUE). P deficiency generally reduced leaf P concentrations and CO2 assimilation rates but efficient cultivars were reducing leaf P concentrations further than inefficient ones while maintaining similar CO2 assimilation rates. Adaptive changes in carbon metabolism were detected but equally in efficient and inefficient cultivar groups. Groups furthermore did not differ with respect to partial substitutions of phospholipids by sulfo‐ and galactolipids. Metabolites significantly more abundant in the efficient group, such as sinapate, benzoate and glucoronate, were related to antioxidant defence and may help alleviating oxidative stress caused by P deficiency. Sugar alcohols ribitol and threitol were another marker metabolite for higher phosphate efficiency as were several amino acids, especially threonine. Since these metabolites are not known to be associated with P deficiency, they may provide novel clues for the selection of more P efficient genotypes. In conclusion, metabolite signatures detected here were not related to phosphate metabolism but rather helped P efficient lines to keep vital processes functional under the adverse conditions of P starvation. Abstract : A set of marker metabolites predictive of high PUE in contrasting groups of efficient and inefficient rice genotypes was identified. These metabolites were not related to carbon, lipid or P metabolism but linked to ROS defence or were sugar alcohols of unknown relation to P.